2021
DOI: 10.1080/00224499.2021.1951643
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Self-Concept Discrepancies Mediate the Relation between Gender Dysphoria Sexual Esteem and Sexual Attitudes in Binary Transgender Individuals

Abstract: Sexual responding in transgender people has typically been investigated from a medical and functional perspective. Aligning with the biopsychosocial model, it is however equally important to consider psychological aspects of sexuality in this population. We propose that the Sexual Self-Concept (SSC) theory offers a valuable framework to understand (sexual) wellbeing in transgender people, while Self-Concept Discrepancy (SCD) theory could offer an explanation of the mechanisms underlying negative SSCs related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Sexual Attraction measures transgender women’s self-evaluation of their own sexual attractiveness as a transgender woman. Individual sexual attractiveness is an important part of their body image ( Hockey et al, 2021 ), and it can also affect the level of an individual’s self-esteem ( Kennis et al, 2021 ). The researchers believe that, for transgender women, subjective feelings of their own sexual attraction are more related to their transgender identity.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual Attraction measures transgender women’s self-evaluation of their own sexual attractiveness as a transgender woman. Individual sexual attractiveness is an important part of their body image ( Hockey et al, 2021 ), and it can also affect the level of an individual’s self-esteem ( Kennis et al, 2021 ). The researchers believe that, for transgender women, subjective feelings of their own sexual attraction are more related to their transgender identity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cisgender women with a history of same-sex sexual experience were higher in sexual entitlement, self-efficacy, and self-reflection ( Boislard and Zimmer-Gembeck, 2011 ). In recent work, transgender individuals scored lower than cisgender individuals on several sexual self-esteem scales (e.g., behavior, body perception, conduct, and attractiveness; Kennis et al, 2021 ). Overall, the results illustrated that transgender individuals have a more negative sexual self-concept ( Kennis et al, 2021 ).…”
Section: Introductionmentioning
confidence: 96%
“…In recent work, transgender individuals scored lower than cisgender individuals on several sexual self-esteem scales (e.g., behavior, body perception, conduct, and attractiveness; Kennis et al, 2021 ). Overall, the results illustrated that transgender individuals have a more negative sexual self-concept ( Kennis et al, 2021 ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The discrepancy between people's perceived real self and what they see as an ideal for themselves has unpleasant consequences for marital relationships and life satisfaction (Robins & Boldero, 2003). Kennis et al (2021) reported that sexual self-concept discrepancy mediated the relationship between gender dysphoria, sexual esteem, and sexual attitudes. "Self" is a fundamental element of human personality and the agent of personal compromise.…”
Section: Introductionmentioning
confidence: 99%